Composite Farming of the Green Mussel, Perna viridis with the Shrimp Penaeus monodon along the Okhamandal Coast of Arabian Sea in Gujarat - N., Subrahmanyam; P., Gopalakrishanan (Fishery Technology, 2025)
The results of an onshore raft-cum-rope culture experiment of green mussel, Perna viridis with shrimp, Penaeus monodon in a shallow sea water pond system are reported. The seed of P. viridis measuring an average of 21.2 mm in length and 1.2 g in weight attained an average of 68.5 mm in length and 24.2 g shell on weight in 150 days of culture. The harvested mussel had a meat content of 32.66%. The results, when compared with the reported data in open sea farming from other parts of the country, were found to be highly encouraging.